Development of Plant Tissue Module Based on Blended Learning as High School Teaching Material - Putri, Raras Widiasri; Retnoningsih, Amin; Widiatningrum, Talitha (Universitas Negeri Semarang)
Plant tissue competence is to analyze the relationship between structure and function of plant tissue. This study aims to test the validity and effectiveness of the plant tissue module based on blended learning. The research method uses research and development (R & D) which consists of research, development, validation, and field-testing. The research was conducted on learning constraints, teaching materials, and learning materials (plant tissues). Modules are developed from the results of research which are then validated and legibility tests. The field test was conducted at SMA N 1 Jepara by taking 3 classes as a control class (without modules), experiment 1 (using modules), and experiment 2 (using blended learning modules). The results of the characteristics of the blended learning module of plant tissue are images and videos in the module derived from the results of research on plant tissue of xerophytes, mesophytes (monocots and dicots), and hydrophytes in the organs of leaves, stems and roots which are presented along with tissue information to facilitate analysis by comparing between tissue. The results of module validation by teaching materials experts are 97% and learning materials experts are 100% with very valid criteria, and module readability validation is 90% with easy to understand criteria. The results of the effectiveness of the module in the cognitive aspects of the experimental class 2 were higher than the control class and experimental class 1, which was 90,90% with very effective criteria. Classical mastery of the psychomotor and affective aspects of the experimental class 2 by 100% with very effective criteria.